2015
DOI: 10.14348/molcells.2015.0221
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the 187 bp EphA7 Genomic DNA as the Dorsal Midline-Specific Enhancer of the Diencephalon and Mesencephalon

Abstract: EphA7 is a key molecule in regulating the development of the dien- and mesencephalon. To get insight into the mechanism of how EphA7 gene expression is regulated during the dorsal specification of the dien- and mesencephalon, we investigated the cis-acting regulatory sequence driving EphA7 to the dorsal midline of the dien- and mesencephalon. Transgenic LacZ reporter analysis, using overlapping EphA7 BACs, was used to narrow down the dorsal midline-specific enhancer, revealing the 25.3 kb genomic region as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…The previously reported gene-related enhancers are mostly hundreds to thousands of base pairs in length ( Abbasi et al, 2010 ; Anwar et al, 2015 ). Interestingly, researchers also found that some enhancers are small, such as a 187 bp dorsal midline-specific enhancer and a 44 bp vit-2 enhancer ( Charité et al, 2001 ; Kim, Park & Park, 2015 ; Goszczynski et al, 2016 ). These studies suggest that some distant and small enhancers are still capable of regulating gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…The previously reported gene-related enhancers are mostly hundreds to thousands of base pairs in length ( Abbasi et al, 2010 ; Anwar et al, 2015 ). Interestingly, researchers also found that some enhancers are small, such as a 187 bp dorsal midline-specific enhancer and a 44 bp vit-2 enhancer ( Charité et al, 2001 ; Kim, Park & Park, 2015 ; Goszczynski et al, 2016 ). These studies suggest that some distant and small enhancers are still capable of regulating gene expression.…”
Section: Introductionmentioning
confidence: 99%